Santo Petrus, Primasi Roma, dan Kepemimpinan Apostolik: Landasan Historis dan Teologis serta Relevansinya bagi Pastoral Gereja Kontemporer - Stefanus Dama Muda; Rikardus Diku Da (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2026)
This paper discusses the Primacy of Saint Peter within the Catholic Church, specifically as the foundation for the Primacy of the Apostolic See of Rome and continuous apostolic leadership. Many question whether the Pope’s leadership truly originates from Christ or is merely a product of historical development. To address this, the study employs a literature review method with hermeneutic and historical approaches, examining Sacred Scripture, the writings of the Church Fathers, and documents from significant councils in Church history. The findings indicate that Saint Peter held a specific role granted directly by Jesus as the rock of the Church, the holder of the keys to the Kingdom of Heaven, and the shepherd of God’s people. This role is transmitted to the Bishops of Rome through apostolic succession, recognized by the early Church and affirmed in various councils, including Nicaea, Ephesus, and Chalcedon. Petrine primacy is not merely symbolic but is manifest in the pastoral life and ministry of the Pope to this day. In the modern Church context, this primacy remains essential for maintaining the unity of faith, serving as a moral voice for the world, and providing spiritual leadership amidst an increasingly complex society.